Dampak PTMT (Pembelajaran Tatap Muka Terbatas) terhadap Kemampuan Membaca Permulaan Siswa Kelas II SDN 98 Palembang - Rian Nata; Dian Nuzulia Armariena; Murjainah Murjainah (Journal on Education, 2023)
This study aims to determine the impact of limited face-to-face learning on the beginning reading ability of class II students at SDN 98 Palembang. This research method uses qualitative, with the research informants being teachers and grade II students at SD Negeri 98 Palembang. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques using qualitative analysis. Based on the results of research and discussion on the impact of PTMT (Limited Face-to-Face Learning) on ​​the beginning reading skills of class II students of SDN 98 Palembang, it can be concluded that PTMT (Limited Face-to-Face Learning) has a positive impact on the beginning reading ability of class II students of SDN 98 Palembang. This is evidenced by students being able to read even though they are still spelling, students have a happy feeling doing limited face-to-face learning compared to online learning. The results of the preliminary reading test showed that 11 students had scored 7-8. The teacher has also carried out the protocol in limited face-to-face learning, namely dividing students into 2 study groups, each group having 2 learning meetings in one week.